A Butterfly‐Inspired Hierarchical Light‐Trapping Structure towards a High‐Performance Polarization‐Sensitive Perovskite Photodetector. Issue 46 (5th September 2019) - Zhan, Yan; Wang, Yang; Cheng, Qunfeng; Li, Chang; Li, Kaixuan; Li, Huizeng; Peng, Jingsong; Lu, Bo; Wang, Yu; Song, Yanlin; Jiang, Lei; Li, Mingzhu
Abstract: Extensive applications for photodetectors have led to demand for high‐responsivity polarization‐sensitive light detection. Inspired by the elaborate architecture of butterfly Papilio paris, a 1D nanograting bonded porous 2D photonic crystal perovskite photodetector (G‐PC‐PD) using a commercial DVD master and 2D crystalline colloidal arrays template was fabricated. The coupling effect from grating diffraction and reflection of the PC stopband renders the enhanced light harvesting of G‐PC‐PD. The porous scaffold and nanoimprinting process afford a highly crystalline perovskite film. White light responsivity and detectivity of G‐PC‐PD are up to 12.67 A W −1 and 3.22×10 13  Jones (6∼7 times that of a pristine perovskite photodetector). The highly ordered nanograting arrays of G‐PC‐PD enable polarization‐sensitive light detection with a rate of −0.72 nA deg −1 . This hierarchical perovskite integrated nanograting and 2D PC architecture opens a new avenue to high‐performance optoelectronic devices. Abstract : The elaborate architecture of the butterfly Papilio paris served as inspiration for the fabrication of a 1D nanograting bonded porous 2D photonic crystal perovskite photodetector (G‐PC‐PD). The coupling effect from grating diffraction and reflection of a PC stopband induces enhanced light harvesting, and the unidirectional 1D nanograting arrays enable the polarization‐sensitive light detection of G‐PC‐PD.